Tales of a city in flames: as the fires closed in on Fort McMurray, some people fled and others waited in Edmonton to help - Silva, Maria (My University, 2016)
It was Monday, May. 1, 2016, in Fort McMurray, and nobody was expecting what was coming. In the afternoon, news organizations like Global TV, CBC and the Edmonton Journal were running stories about a fire that had reached the city. Twitter was full of it. It made my heart race. My mother had been working at camp in the area for over four years. I was worried and scared. All I could think about was the worst-case scenario: death. I didn’t look very deeply into the stories because all I cared about was whether she was safe.
Keywords: disaster response